A reduction in metabolism explains the tradeoffs associated with the long‐term adaptation of phytoplankton to high CO2 concentrations. Issue 5 (4th January 2022) - Jin, Peng; Ji, Yan; Huang, Quanting; Li, Peiyuan; Pan, Jinmei; Lu, Hua; Liang, Zhe; Guo, Yingyan; Zhong, Jiahui; Beardall, John; Xia, Jianrong
Summary: Phytoplankton are responsible for nearly half of global primary productivity and play crucial roles in the Earth's biogeochemical cycles. However, the long‐term adaptive responses of phytoplankton to rising CO2 remains unknown. Here we examine the physiological and proteomics responses of a marine diatom, Phaeodactylum tricornutum, following long‐term ( c . 900 generations) selection to high CO2 conditions. Our results show that this diatom responds to long‐term high CO2 selection by downregulating proteins involved in energy production (Calvin cycle, tricarboxylic acid cycle, glycolysis, oxidative pentose phosphate pathway), with a subsequent decrease in photosynthesis and respiration. Nearly similar extents of downregulation of photosynthesis and respiration allow the high CO2 ‐adapted populations to allocate the same fraction of carbon to growth, thereby maintaining their fitness during the long‐term high CO2 selection. These results indicate an important role of metabolism reduction under high CO2 and shed new light on the adaptive mechanisms of phytoplankton in response to climate change.